Application of Public Service Motivation to non- western countries Understanding the Role of Culture and Values (International Journal of Food and Nutritional Sciences, 2022)
Public Service Motivation has gained traction among public administration scholars ever since Perry provided a measurement scale to account for the motivation profile of public service employees. However, the PSM as we know it today is primarily the product of western scholarship